Electrical and Structural Adaption of Athlete’s Heart and the Impact on Training and Recovery Management in Professional Basketball Players: A Retrospective Observational Study - Zimmermann, Paul; Moser, Othmar; Edelmann, Frank; Schöffl, Volker; Eckstein, Max L.; Braun, Martin (Frontiers in Physiology, 2022)
The primary aim of our retrospective study was to evaluate cardiac remodeling by electrocardiogram- (ECG), echocardiographic-, and cardiopulmonary exercise testing (CPET) analyses in professional basketball players. We hypothesized to find different effects of basketball training on cardiac functional and structural remodeling as well as different outcomes in CPET in athletes with early repolarization pattern (ER) and players without ER pattern (no ER). Therefore we divided the cohort into a group with signs of ER pattern and without these criteria and presented the differences in detail. This was a single-center, retrospective study performed in twenty-seven professional basketball players (age: 26.5 ± 7.5 years, male: 27, height: 197.2 ± 12 cm, weight: 100 ± 17 kg, BMI: 25.7 ± 3.4 kg/m2). All participants underwent a cardiological sports medicine check-up between 2015 and 2019 during their pre-season preparation time. Data were analyzed using analysis of variance testing (ANOVA) with post-hoc testing and unpaired t-testing (p ≤ 0.05). Retrospectively additional information was collected referring to the management of training sessions, recovery time and nutrition of the professional basketballers. Comparing professional basketball players with ER pattern to those with no ER pattern, significant differences were found for echocardiographic- and CPET analyses. Absolute and relativized peak oxygen uptake (VO2 peak, p = 0.018) and maximum workload during CPET (p = 0.026) were higher in athletes with an ER pattern. Furthermore, ER pattern athletes showed a higher enddiastolic left ventricular diameter (LVedd; p = 0.048) and a significantly biatrial remodeling, as left atrial- (LA, p = 0.006) and right atrial remodeling (RA, p =0.033). Significant differences between the two compared groups were proven for left ventricular mass Index (LVMI gr/m2; p = 0.002). Professional basketball players with criteria of ER pattern showed different results in CPET and cardiac remodeling as athletes with no ER pattern. These findings should encourage the athletic training staff to emphasize the quality of an individual training schedule for each athlete based on the cardiopulmonary pre-season sport medicine checkup. Nevertheless, echocardiographic findings, ER pattern and performance in CPET have to be interpreted referring the sport specific and athlete´s ethnical background.